Willingness to vaccinate against herpes zoster in Chinese urban population: a mixed-methods study - Ping He; Beibei Yuan; Dawei Zhu; Ming Wang; Yanshang Wang; Mingzheng Hu; Chao Long; Yiqi Xia; Weiying Zhao (BMJ Open)
Objective Although the herpes zoster vaccine has been available in mainland China since June 2020, residents’ knowledge of herpes zoster and the herpes zoster vaccine is poor, and vaccination rates are low, especially among the elderly, who are at high risk for herpes zoster. This study assessed willingness to be vaccinated against herpes zoster and factors associated with vaccination among urban residents in China.Methods A mixed-methods study was conducted in community health centres from August 2022 to September 2022. We used convenience sampling to select 2864 residents from 9 Chinese cities for the quantitative study and 67 adults for the qualitative study. A structured questionnaire was used for the quantitative study, and data were collected through face-to-face interviews. Multinomial logistic regression was used to analyse factors associated with willingness to vaccinate. Qualitative data were analysed using thematic analysis of barriers to herpes zoster vaccination.Results A total of 2864 eligible respondents were included in the study. Of these, 42.67% intended to receive the herpes zoster vaccine, 21.44% refused and 35.89% were hesitant. The results of the quantitative and qualitative analyses showed that the factors associated with respondents’ willingness to be vaccinated against herpes zoster included: personal characteristics such as gender, age and income; knowledge and attitudes about herpes zoster and the vaccine; vaccine characteristics such as efficacy, safety and price; and other factors such as pain tolerance and accessibility to vaccination.Conclusion The low willingness to vaccinate, especially among the elderly, is mainly related to their poor knowledge and negative attitude towards the infection and vaccination. Therefore, health education about herpes zoster, immunisation promotion, and improvement of accessibility and affordability would be valuable in China.